Organofluorine compounds in biology and medicine - Reddy, V. Prakash (Elsevier, 2015)
This book covers topics on biochemically relevant organofluorine compounds and their synthesis and biochemical pathways. Organofluorine compounds have renewed interest in pharmaceutical industry, and therefore a concise book on this topic is highly relevant to the scientific community involved in this area.